2006
DOI: 10.1002/cncr.22246
|View full text |Cite
|
Sign up to set email alerts
|

Focal and craniospinal irradiation for patients with intracranial germinoma and patterns of failure

Abstract: Disease Overview: Acute myeloid leukemia (AML) results from accumulation of abnormal immature cells in the marrow. These cells interfere with normal hematopoiesis can escape into the blood and infiltrate lung and CNS. The most common cause of death is bone marrow failure. It is likely that many different mutations and/or epigenetic aberrations can produce the same disease, with these differences responsible for the very variable response to therapy, which is AML's principal clinical feature. Diagnosis: This re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(22 citation statements)
references
References 38 publications
1
21
0
Order By: Relevance
“…1,4,12,19,20,24,32 Tumor control and excellent functional outcome rates were achieved in 90% of 16 patients with pure germinoma treated with cisplatin-based chemotherapy, followed by 24 Gy of focal radiation therapy to the tumor site for solitary germinoma, the whole ventricle for multifocal germinoma, and the craniospinal axis for disseminated germinoma. 1 However, the combination of cisplatin-based chemotherapy and 24-30 Gy of focal radiation therapy to the primary tumor site with 1-2 cm margins resulted in an increased recurrence rate up to 20-44%.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…1,4,12,19,20,24,32 Tumor control and excellent functional outcome rates were achieved in 90% of 16 patients with pure germinoma treated with cisplatin-based chemotherapy, followed by 24 Gy of focal radiation therapy to the tumor site for solitary germinoma, the whole ventricle for multifocal germinoma, and the craniospinal axis for disseminated germinoma. 1 However, the combination of cisplatin-based chemotherapy and 24-30 Gy of focal radiation therapy to the primary tumor site with 1-2 cm margins resulted in an increased recurrence rate up to 20-44%.…”
mentioning
confidence: 99%
“…1 However, the combination of cisplatin-based chemotherapy and 24-30 Gy of focal radiation therapy to the primary tumor site with 1-2 cm margins resulted in an increased recurrence rate up to 20-44%. 24,32 In addition, we previously reported a case of recurrent intracranial germinoma outside the initial radiation field with progressive malignant transformation. 16 Therefore, neoadjuvant reduced-field radiation therapy not covering the whole ventricle may be associated with increased risk of recurrence, and radiation therapy to cover the whole ventricle is essential for longterm tumor control.…”
mentioning
confidence: 99%
“…Fouladi et al [45] reported there were similar effects of CSI on the regimen of carboplatin and etoposide chemotherapy (2-3 cycles) plus local field radiotherapy (total dose: 25-35 Gy) with a similar 5-year survival rate. Nguyen et al [46] reported the same 5-year survival rate of both CSI and chemotherapy followed by local field radiotherapy. However, this combined therapy was found to be co-related with spinal tumor recurrence.…”
Section: Chemotherapymentioning
confidence: 78%
“…Overall survival at 5 years is 90% [1,2,3,12]. The optimal treatment of IG is still a matter of debate [13,14].…”
Section: Discussionmentioning
confidence: 99%
“…Intracranial germinomas (IG) are rare tumors which at first diagnosis are highly curable with radiotherapy alone or a combination of radiotherapy and chemotherapy [1,2,3]. Recurrence and dissemination are seen in about 10-20% of cases, in the vast majority occurring within the first 2 years after diagnosis, whereas late recurrences are rare events [4,5,6,7].…”
Section: Introductionmentioning
confidence: 99%